2020
DOI: 10.1021/acsanm.0c00071
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Modulation on the Growth of Urchin-like Na2Ti3O7 Microspheres for Photothermally Enhanced H2 Generation from Ammonia Borane

Abstract: Structural optimization and surface engineering of photocatalysts are considered as promising approaches to improve their performances effectively. The precise control of morphology and compositions during synthesis of photocatalysts is important but yet challenging. In this work, without any aid of surfactant, urchin-like reduced graphene oxide/sodium titanate (RGO/ Na 2 Ti 3 O 7 ) microspheres were fabricated by a facile, one-pot hydrothermal reaction with good reproducibility. Both microsized and nanosized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…An alternative process to generate hydrogen proposed in this current year by Dai and by Naldoni is the photo-thermally enhanced hydrolysis of ammonia borane, whose hydrogen content is 19.6%. [266][267][268] Wu et al prepared a series of urchin-like sodium titanate microspheres supported on the reduced graphene oxide (RGO/Na 2 Ti 3 O 7 ) photo-thermal catalyst with different graphene oxide content (0, 33, 50, 60, 66 wt%). 266 Particularly, they focused on the challenging aspect of synthesis optimization, elucidating the role of graphene oxide sheets in the growth mechanism of Na 2 Ti 3 O 7 microspheres.…”
Section: H 2 Evolution and Other Processes Driven By Photo-thermal Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative process to generate hydrogen proposed in this current year by Dai and by Naldoni is the photo-thermally enhanced hydrolysis of ammonia borane, whose hydrogen content is 19.6%. [266][267][268] Wu et al prepared a series of urchin-like sodium titanate microspheres supported on the reduced graphene oxide (RGO/Na 2 Ti 3 O 7 ) photo-thermal catalyst with different graphene oxide content (0, 33, 50, 60, 66 wt%). 266 Particularly, they focused on the challenging aspect of synthesis optimization, elucidating the role of graphene oxide sheets in the growth mechanism of Na 2 Ti 3 O 7 microspheres.…”
Section: H 2 Evolution and Other Processes Driven By Photo-thermal Catalysismentioning
confidence: 99%
“…[266][267][268] Wu et al prepared a series of urchin-like sodium titanate microspheres supported on the reduced graphene oxide (RGO/Na 2 Ti 3 O 7 ) photo-thermal catalyst with different graphene oxide content (0, 33, 50, 60, 66 wt%). 266 Particularly, they focused on the challenging aspect of synthesis optimization, elucidating the role of graphene oxide sheets in the growth mechanism of Na 2 Ti 3 O 7 microspheres. Also, they found that the photoelectrochemical performance of the prepared materials was related to the structural organization of the catalyst and the surface features of the Na 2 Ti 3 O 7 microspheres.…”
Section: H 2 Evolution and Other Processes Driven By Photo-thermal Catalysismentioning
confidence: 99%
“…Visible-light acceleration of a number of various catalytic reactions of synthetic and environmental interest has been reported for plasmonic gold as part of heterobimetallic catalysts. 12 In particular, interest has recently focused on plasmon induced light acceleration of hydrolysis of ammonia-borane (AB), NH3BH3, by coinage metal NPs using heterobimetallic nanocatalysts either coupled to [13][14][15][16][17][18] or without a semi-conductor. [19][20][21][22][23] Inorganic hydrides such as AB and sodium borohydride, NaBH4, are promising hydrogen storage compounds, [24][25][26] because they are stable solids with high colloidal solubility in water, contain a high proportion of hydrogen and are easily transported contrary to explosive hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…We have summarized a number of representative PTC works involving different fields, as shown in Table 1 . [ 33,36,38‐47,49‐57,61‐68,70‐73,75‐81,83,85,87‐89,94,111‐113,115,117,118,120,121,123‐168 ] The PTC works are categorized into three major fields, solar fuel production, chemical synthesis, and environmental remediation, and the catalysts and energy sources used in the studies, along with the reaction temperatures and reaction results are collected. Besides, the datasets of the temperatures and the reaction results have been extracted and plotted for better visibility, as shown in Figure .…”
Section: Important Issues In Ptcmentioning
confidence: 99%